Effects of Indomethacin and Celecoxib on renal function in athletes - Baker, J.; Cotter, J. D.; Gerrard, D. F.; Bell, M. L.; Walker, R. J. (Medicine & Science in Sports & Exercise, 2005)
Introduction: Strenuous exercise induces a marked reduction in renal hemodynamics. Prostaglandins (PG) play an important role in maintaining renal integrity in the face of hemodynamic changes. Inhibition of cyclooxygenase (COX) and thus PG formation can further compromise renal perfusion. The role of selective COX-2 inhibition on renal hemodynamics during exercise has not been investigated.